Pain in Covid Era - Alonso-Matielo, Heloísa; da Silva Oliveira, Victória Regina; de Oliveira, Victhor Teixeira; Dale, Camila Squarzoni (Frontiers in Physiology, 2021)
The Covid19 pandemic has impacted the lives and health of persons worldwide and although majority of Covid19 patients present with respiratory symptoms, pain emerges as an important feature of Covid19 infection. About 15 to 20% of patients progress to a severe condition that requires hospitalization. Although the disease was initially reported as a respiratory syndrome, other systems such as cardiovascular, renal and nervous systems may be affected in the acute stages, increasing the need for continuous support to treat multiple sequelae caused by the disease. Due to the severity of the disease, damages found after discharge should also be considered. Providing multidisciplinary interventions promoting physical and psychological recovery in the first stages of hospitalization can minimize these damages. Cognitive, physical and psychological dysfunction reported by Covid19 patients after discharge can have profound effects on quality of life. Pain is usually part of this dysfunction, but it is still poorly understood how it affects survivors of Covid19 infections. There is limited information about the clinical characteristics, treatment and outcome of maintenance of pain in Covid19 patients. The purpose of this narrative review is to provide an overview of the implications of Covid19 on acute and chronic pain states